The Implementation Of Duties & Functions Of Immigration Office In Granting Statement Permits Of Foreign Citizens - Septarina Nur Handayani; Sri Endah Wahyuningsih (Jurnal Daulat Hukum, 2020)
This study aims to determine the duties and functions of the Immigration Office in granting residence permits for foreign citizens, enforcing immigration laws against violations of residence permits for foreign nationals and knowing the obstacles and efforts made by the Immigration Office in granting residence permits for foreign citizens.This research uses an approach method Normative juridical which refers to the applicable laws and regulations by examining secondary data against the principle of immigration law, namely Act No. 6 of 2011 as well as case studies at the immigration office.Based on the research results, it can be concluded that the implementation of granting residence permits for foreign nationals at the Immigration Office is in accordance with the provisions stipulated in Act No.6 of 2011 concerning Immigration and related regulations as the executor. For foreign citizens who do not obey the rules, the Immigration Office can enforce the law to create state security and discipline. The obstacles faced are limited human resources, limited infrastructure, communication and administration. Efforts to overcome obstacles include: multiple assignments, procurement of generators, bringing in interpreters according to language, providing assurance of the issue of residence permits.        Keywords: Immigration; Foreign Citizens; Residence Permit; Security and Discipline.